TEN-T Corridors – Stairway to Heaven or Highway to Hell? - Kathrin Goldmann; Jan Wessel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The European Union coordinates and co-finances supra-national transport infrastructure investments in the Trans-European Transport Network (TEN-T) which consist of road, rail, airport, and port infrastructure. To the best of our knowledge, we are the first to quantify the direct and indirect economic growth effects of newly created TEN-T core corridor roads in Eastern European countries. Both the panel data and the spatial analyses show that regional GDP growth at the NUTS3 level is between 0.4 and 2.4 percentage points higher, if a region has direct access to a newly built road. The analyses with a spatial Durbin model (SDM), for which we use three differently specified spatial weight matrices, show that the new construction of a TEN-T core road also causes positive spillover effects on adjacent regions, as well as on regions that are connected by the same corridor section. The results thus indicate that the TEN-T policy, which aims to alleviate transport bottlenecks, can help to increase cohesion between central and peripheral regions and consequently to enhance regional welfare in Eastern Europe.
Keywords: R42; O18; O47; 330; transport infrastructure; TEN-T corridors; supra-national infrastructure investment; spatial Durbin model